PENGARUH ACTIVITY DAILY LIVING (ADL) TERHADAP NYERI SENDI PADA LANSIA - Agitya Dwi Septadani (FKU 15 UMY 603, 2015)
Joint pain is a major problem that will affect the daily activities in the elderly. One way to reduce joint pain in the elderly is by doing physical exercise motion. The aim of this study was to analyze the influence of daily activities to decrease joint pain by using quasy experimental design. The study population was elderly people aged 60-74 years living in Surodikraman, Ponorogo with samples taken by purposive sampling technique, totaling 26 people treatment group who had met the inclusion criteria. The independent variable in this research is to perform Activity Daily Living (ADL), and the dependent variable was the elderly with symptoms of joint pain. Data taken using observation sheets and questionnaires, to determine the level of joint pain with a pain scale numerical, data analysis Shapiro Wilk normality test and Paired Simple T test to assess the significance of the treatment group pre-treatment and post-treatment, with a significance value of p <0, 05, of 26 elderly, 24 people in decreased joint pain. Statistical test results Paired Simple T test showed no significant differences after the activity (p = 0.001), and Paired Simple T test showed no significant difference between before treatment and after treatment, so that it can be concluded that the Activity Daily Living (ADL) can reduce joint pain in the elderly. Further research needs to be done by using more respondents and more time so that the results are more accurate. Keywords: Activity Daily Living, joint pain, the Elderly